Analisis Pengaruh Ukuran Perusahaan, Jenis Industri, Umur Perusahaan, Dan Penerbitan Sukuk Terhadap Tingkat Pengungkapan Islamic Social Reporting (Isr) Pada Perusahaan Yang Terdaftar di Daftar Efek Syariah (Des) Tahun 2010-2012 - Devi Citravury; Sri Mulyati; Icih Icih (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2019)
The research aim of this study is to obtain an empirical evidence about factor that affect Islamic Social Reporting (ISR) in company’s annual report. The factors that used in this study such as: industry size, type industry, age of firm and issuance of Sukuk. Measurement of Islamic Social Reporting is based Islamic Social Reporting Index asseen from the company’s annual report. Populations in this study are all companies that listed in Shariah Securities (Daftar Efek Syariah-DES). DES are collection of securities that are not contradict with Islamic principles and have been approved by BAPEPAM and LK. The sampling method in thistudy is purposive sampling. The total number of samples in this study were 63 research samples. The analytical techniques was conducted by multiple regression method and also classical assumption test. The analysis showed that industry size, type industry, and age of firm significantly positive influence the the level of disclosure of Islamic Social Reporting (ISR) in Indonesia. Meanwhile, issuance of Sukuk had no effect to the level of disclosure of Islamic Social Reporting (ISR) in Indonesia.